2017
DOI: 10.1016/j.leukres.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy in multiple myeloma

Abstract: Autophagy plays an important role in plasma cell ontogeny and in the pathophysiology of multiple myeloma. Autophagy is usually considered a pro-survival mechanism, and cooperates with the ubiquitin proteasome system in maintaining the homeostasis of myeloma cells by degrading excessive and misfolded proteins for energy recycling. Therefore, the inhibition of autophagy could effectively induce death in myeloma cells, and could synergize with proteasome inhibitors. However, the excessive activation of autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 72 publications
0
44
0
1
Order By: Relevance
“…Literature data focus on autophagy as an MM prosurvival mechanism able to exert a protective effect under drug treatment in that drug-resistant MM cells can escape the toxic effect of drugs via autophagy [92] . Proteasome inhibitors, such as bortezomib and carfilzomib, are the first-line drug for MM treatment in both newly diagnosed and relapsed patients.…”
Section: Autophagy As Prosurvival Machinery In MMmentioning
confidence: 99%
“…Literature data focus on autophagy as an MM prosurvival mechanism able to exert a protective effect under drug treatment in that drug-resistant MM cells can escape the toxic effect of drugs via autophagy [92] . Proteasome inhibitors, such as bortezomib and carfilzomib, are the first-line drug for MM treatment in both newly diagnosed and relapsed patients.…”
Section: Autophagy As Prosurvival Machinery In MMmentioning
confidence: 99%
“…15 In MM, autophagy induced by chemotherapeutic drugs can either play a cytoprotective role, through relieving cellular stress caused by toxic insult, or play a cytotoxic role, through triggering autophagy-related cell death. 16 Moreover, previous studies have shown that Dex-induced cell death in lymphoid leukemia is mediated through the initiation of autophagy. Induction of autophagy is required for acute lymphoblastic leukemia cells to overcome glucocorticoid resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, activation of autophagic cell death may represent a promising approach for treatment of MM (32)(33)(34)(35)(36). Recent studies have demonstrated that autophagy mediates drug resistance in MM cells and leads to development of clinical complications for MM, while inhibition of autophagy may reverse the response to drugs (37,38). However, the clinical role, particularly the prognostic role of ARGs in MM, has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%